National Hospital Discharge Survey, 1989 ([Verlag nicht ermittelbar], 1994)
The National Hospital Discharge Survey (NHDS) collects medical and demographic information annually from a sample of hospital discharge records. Variables include the patients' demographic characteristics (sex, age, race, marital status), dates of admission and discharge, status at discharge, final diagnoses, surgical and nonsurgical procedures, dates of surgeries, and sources of payment. Information on hospital characteristics such as bedsize, ownership, and region of the country is also included.